Surgical Stabilization of Rib Fractures: Indications, Techniques, and Pitfalls. Issue 2 (2020) - Fokin, Alexander A.; Hus, Nir; Wycech, Joanna; Rodriguez, Eugenio; Puente, Ivan
Abstract : Background: Rib fractures are a common thoracic injury that is encountered in 20% to 39% of patients with blunt chest trauma and is associated with substantial morbidity and mortality1, 2 . Traditionally, the majority of patient with rib fractures have been managed nonoperatively. Recently, the utilization of surgical stabilization of rib fractures has increased considerably because the procedure has shown improved outcomes3 -5 . Description: Surgical stabilization should be considered in cases of multiple bicortically displaced rib fractures, especially in those with a flail chest and/or a concomitant ipsilateral displaced midshaft clavicular fracture or sternal fracture, as such cases may result in thoracic wall instability. For surgical stabilization of rib fractures, we classify rib fractures by location, type of fracture, and degree of displacement after obtaining thin-sliced chest computed tomography (CT) scans. The incision is selected depending on the fracture location, and the surgical technique is chosen relevant to the type of fracture. Single-lung intubation is preferred if there is no severe contralateral pulmonary contusion. We favor performing video-assisted thoracoscopy if possible to control bleeding, evacuate hematomas, repair a lung, and perform cryoablation of the intercostal nerves. A lateral approach is considered to be the main surgical approach because it allows access to the majority of rib fractures. A curvilinear skin incision is made overlying the fractured ribs. Posterior rib fractures are exposed through a vertical incision within the triangle of auscultation, and anterior fractures, through a transverse inframammary incision. The muscle-sparing technique, splitting alongside fibers without transection, should be utilized if possible and supplemented by muscle retraction. For surgical stabilization of rib fractures, we currently prefer precontoured side and rib-specific plates with threaded holes and self-tapping locking screws. Polymer cable cerclage is used to enhance plating of longitudinal fractures, rib fractures near the spine, osteoporotic ribs, and injuries of rib cartilage. The third to eighth ribs are plated most often. Intercostal muscle deficit, if present, is repaired with a xenograft patch. In comminuted rib fractures, the bone gap is bridged with bone graft. Surgical stabilization of rib fractures is recommended within the first 7 days after trauma, preferably within the first 3 days6 -8 . Alternatives: Nonoperative treatment alternatives include (1) epidural analgesia when not contraindicated because of anticoagulant venous thromboembolism prophylaxis9, 10 ; (2) thoracic paravertebral blockage, e.g., serratus anterior or erector spinae plane nerve block11, 12 ; (3) intercostal nerve block; (4) intravenous or enteral analgesics, e.g., opioids, acetaminophen, and nonsteroidal anti-inflammatory drugs (NSAIDs); (5) intrapleural analgesia, e.g., bupivacaine infusion; and (6) multimodal analgesia that incorporates regional techniques, systemic analgesics, and analgesic adjuncts9 . Rationale: Surgical stabilization of rib fractures is a safe and effective method to treat displaced rib fractures. The procedure provides definitive stabilization of fractures, improves pulmonary function, lessens pain medication requirements, prevents deformity formation, and results in reduced morbidity and mortality.